Exploring persuasive technology to enhance delivery of professional services - Omar Basamh, Saeed Salem; Ali, Faisal; Huq, MdNajibul; Ibrahim, Jamaludin (Centre for Promoting Ideas, USA, 2013)
In this paper we aim to explore Persuasive Technology in depth and how it will enhance the delivery of professional services. A computer is a device that can be programmed to carry out and process a number of arithmetic and logical operations. Computers as Technology have changed from normal usage to become persuaders that focuses on how to design interactive services and technologies to sway people's attitude and support positive in their behavior. They can be persistence, can use many modalities, allows for anonymity, and has the ability to be almost everywhere. Besides, due to these mentioned reasons, technology can gain a competitive advantage in persuasion and various types of tools like reduction, tailoring, tunneling, suggestion, and condition; that make computers an effective persuasive tool. Moreover, there are a number of principles that are adopted by computers to enhance persuasion through connectivity and mobility including: mobile-marriage, information quality, social facilitation and competition. Professional Service (PS) is a unique function performed by independent contractors or consultants whose occupation is the rendering of such services. Professional services are delivered through expert, skilled, and knowledgeable individuals from different fields, locally and globally. The persuasive technology can assists in enhancing the delivery of professional services to clients or customers. Understanding the market and individual needs of technology. Numbers of recommendations were suggested that would assist in enhancing the delivery of Professional Services through persuasive technology.